EFEKTIVITAS PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AL QUR’AN HADIST DI KELAS IX MTS SALAFIYAH SYAFIIYAH BANDUNG DIWEK JOMBANG - Nur Hamidatul Arifah; Hidayatur Rohmah (JoEMS (Journal of Education and Management Studies), 2020)
This study aims to determine students' motivation towards the use of audio-visual media in the Al-Qur'an Hadith subjects at MTs Salafiyah Syafiiyah Bandung. To achieve these objectives the researchers used data collection techniques through interviews, questionnaires, and documentation. The data is processed using quantitative analysis to determine the effect of learning media on student motivation. This research includes the type of field research or the field of research that is the author conducts research directly to the location to obtain and collect data. The results showed that the level of use of instructional media was classified in either category. The level of student learning motivation is classified as "weak or sufficient" in terms of the average results of 65.30. The results of the hypothesis test indicate that the value of Sig. (2.tailed) <0.05 then there is a correlation between the use of audio visual media with student learning motivation is 0,000 <0.05 which means there is a significant correlation. The effectiveness of the use of audio visual media in MTs Salafiyah Syafiiyah Bandung is still relatively weak on student motivation, which is 15.6%. From the hypothesis testing and calculation of Pearson Correlation, it can be concluded that the use of audio visual media is said to be quite effective and can significantly influence student motivation.